Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages houses." There have even been instances of builders owning land asking by circular for donations to the legal costs involved in fighting the local authority! The land is generally acquired but the process involves many months, and in the meantime no houses can be built. As for the building industry, both in the erection and materials sections, there is a record of bad wages and bad conditions. The Government has endeavoured to overcome the turmoil by patchwork agreements, but the basic economic fact remains that the workers are labour units from which profits are made. The constant struggle between employers and workers continues. The workers have no say in housing policy, either in theory or in practice : there is no incentive to work in the interest of the community when the industries continue to be operated for private profit instead of human need. Whilst the application of common ownership and workers control is the only real solution, the Labour Government in the last year could have attempted to set up production committees to achieve the utmost co-operation and understanding on building sites, and in works and factories. Remembering the boom and slump periods following the 1914-18 war, the Labour Government could have produced and publicised a national housing scheme which would have enabled the workers to see a greater degree of security than has been their lot in the past. Sabotage by builders who are determined to exact their own terms in return for their co-operation in the housing drive : the burdening of local authorities with interest charges (amounting in the vast majority of cases to 60 per cent. or 70 per cent. of income) : the loading of one Minister, a good socialist handicapped by lack of socialist power, with two tremendous jobs : the continued activities of price rings in the materials' industries : the many inefficient or unwilling Councils throughout the country : the failure to create many worth-while direct labour organisations : these are but a few of the disturbing factors in the housing situation after the Labour Government's first twelve months. It is vital that the Government should summon up its courage and apply socialism to a task involving the happiness and health, mental and physical, of millions of people. If another year passes with the same timid handling then only tragedy can result. 17 15X/2/98/21